Nachhaltige Bildung in der Grundschule - Haider, Michael; Böhme, Richard; Gebauer, Susanne; Gößinger, Christian; Munser-Kiefer, Meike; Rank, Astrid (Jahrbuch Grundschulforschung, 2023)
Sustainable education in primary school can be viewed from several angles: In a broad understanding of the term, the topic refers to sustainable educational processes in the sense of long-term availability. This plays a special role for the primary school as the first school with its mission of basic education. At the same time, a narrow conceptual understanding is included, which considers education for sustainable development from an ecological, economic and social perspective. In this context, action aims at a more sustainable and just present and future. The present volume compiles contributions from the 30th annual conference of the Commission for Primary School Research and Primary Education, which took place in Regensburg in September 2022 and addressed the topic of "Sustainable Education in Primary Schools".